2015
DOI: 10.1002/smll.201501907
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Patterning of Cells with a Microeraser and Electrospun Nanofibers

Abstract: For tissue engineering applications, it is important to develop fabrication strategies for building models with controlled cell distributions in defined structures. Here, a simple, flexible approach (named the μ-eraser strategy) is developed to construct multicell micropatterns. This approach involves pressing a poly(dimethylsiloxane) stamp to erase cells growing on substrates, and seeding other types of cells. The pressing/seeding process can be conducted in any designed pattern at desired time point. In a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…A coculture system with a precisely controlled microenvironment is often used to understand how cancer cells affect properties of noncancerous cells, and vice versa, affecting them either directly through physical/chemical cell–cell interactions or indirectly through soluble cytokines. To mimic these coculture systems, cell micropatterning using the μ-eraser technique or stencil micropatterning technique has been developed. Zhong et al have cultured lung cancer cells (A549) on poly­(lactide- co -glycolide) (PLGA) and then removed A549 cells in specific regions by pressing cell layers with a PDMS stamp .…”
Section: Cancer Mechanosensationmentioning
confidence: 99%
“…A coculture system with a precisely controlled microenvironment is often used to understand how cancer cells affect properties of noncancerous cells, and vice versa, affecting them either directly through physical/chemical cell–cell interactions or indirectly through soluble cytokines. To mimic these coculture systems, cell micropatterning using the μ-eraser technique or stencil micropatterning technique has been developed. Zhong et al have cultured lung cancer cells (A549) on poly­(lactide- co -glycolide) (PLGA) and then removed A549 cells in specific regions by pressing cell layers with a PDMS stamp .…”
Section: Cancer Mechanosensationmentioning
confidence: 99%
“…A contact-erasing system—termed µ-eraser strategy—has been engineered to fabricate a co-culture micropattern arrangement, which involves pressing a stamp to induce cell lysis and then seeding another type of cell on the empty regions. 61 The incorporation of a fluorescent lipophilic dye into one of the cell types would then make it possible to seed two cellularly distinguishable populations. Non-labelled cells could be specifically irradiated using partial shielding with a grid that resembles the original cell pattern.…”
Section: The Bystander Effectmentioning
confidence: 99%
“…In another study, Khademhosseini et al made reversibly sealed microfluidic channels to form a multiphenotype array of cells on the substrate . Another research group reported a micro-eraser strategy to form multicell micropatterns . They pressed a poly­(dimethylsiloxane) stamp to erase growing cells and then seeded a second cell type on the same substrate.…”
Section: Introductionmentioning
confidence: 99%
“…43 Another research group reported a microeraser strategy to form multicell micropatterns. 44 They pressed a poly(dimethylsiloxane) stamp to erase growing cells and then seeded a second cell type on the same substrate. They also studied the effect of microstripes and nanofibers on cell orientation and migration.…”
Section: Introductionmentioning
confidence: 99%